The genera Coccus and Prococcus (Hemiptera: Coccomorpha: Coccidae) in China, with two new combinations and descriptions of two new species - Cao, Tong; Watson, Gillian W.; Hodgson, Chris J.; Jing, Qi; Feng, Ji-Nian (Zootaxa, 2022)
The Chinese soft scale species in the genus Coccus Linnaeus, 1758 (Hemiptera: Coccomorpha: Coccidae) were studied. Coccus cambodiensis Takahashi and the Malaysian species C. cameronensis Takahashi are considered to be non-congeneric with Coccus hesperidum Linnaeus, 1758, the type species of Coccus, and are transferred to Prococcus Avasthi, 1993, as Prococcus cambodiensis (Takahashi, 1942), comb. n. and Prococcus cameronensis (Takahashi, 1952), comb. n. The generic diagnosis of Prococcus is revised. In the genus Coccus, two new species are described and illustrated based on adult females: Coccus nanningensis Cao & Feng, sp. n. from Guangxi, China, on Ficus carica (Moraceae), and Coccus cephalotaxus Cao & Feng, sp. n. from Shannxi, China, on Cephalotaxus sinensis (Taxaceae). Identification keys to separate adult females of Prococcus from Coccus, the 14 species of Coccus found in China, and all three species of Prococcus are provided.